2010
DOI: 10.1167/iovs.09-4555
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Multifocal Electroretinographic Implicit Times in the Ocular Ischemic Syndrome

Abstract: PURPOSE.To examine retinal function in chronic ocular ischemia using multifocal electroretinography (mfERG). METHODS. Thirteen patients with unilateral ocular ischemic syndrome (OIS) underwent assessment of ophthalmic systolic blood pressure by ocular pneumoplethysmography, carotid artery patency by ultrasonography, intraocular pressure (IOP) by applanation tonometry, retinal perfusion by fluorescein angiography, and retinal function by mfERG. RESULTS. Ophthalmic systolic blood pressure was 67.0 Ϯ 11.6 mm Hg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…A significant delay of the first‐order summed N1 and P1 implicit times and a significant decrease in N1 and P1 amplitudes was seen with increasing degrees of carotid artery stenosis. This new observation found within patients with asymmetric carotid artery stenosis and clinically healthy eyes follows a pattern previously observed between patients with the ocular ischaemic syndrome eyes (Kofoed et al. 2010b).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A significant delay of the first‐order summed N1 and P1 implicit times and a significant decrease in N1 and P1 amplitudes was seen with increasing degrees of carotid artery stenosis. This new observation found within patients with asymmetric carotid artery stenosis and clinically healthy eyes follows a pattern previously observed between patients with the ocular ischaemic syndrome eyes (Kofoed et al. 2010b).…”
Section: Discussionsupporting
confidence: 88%
“…1983; Russell & Ikeda 1986; Brown & Magargal 1988) and subnormal oscillatory potentials (Story et al. 1995) as well as prolonged implicit times of the N1, P1, and N2 potentials of the multifocal electroretinogram (Kofoed et al. 2010b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Kofoed et al identified significant delays in all first-order summed implicit times and a clear trend towards reduced amplitudes in mfERG compared with healthy controls [26]. In the present study, we demonstrated that even in the absence of the clinical signs of ocular ischemic syndrome, significant ICAS may be associated with retinal function abnormalities.…”
Section: Discussionsupporting
confidence: 66%
“…Ophthalmologic studies such as visual-evoked potentials (VEP), electroretinography (ERG) and ophthalmotonometry are rarely used to establish the diagnosis of OIS [4,21]. …”
Section: Diagnosismentioning
confidence: 99%